A sociological analysis of the origin and development of the Jehovah's Witnesses and their schismatic groups - Rogerson, A; Rogerson, Alan Thomas (1972)
This thesis is intended as a contribution to the field of the Sociology of Religion, in particular the study of Christian sects. It examines in a historical and sociological framework the origins and development of the Jehovah's Witnesses and their schismatic groups, concentrating on the period 1868-194-2. This thesis draws on extensive primary sources to construct a more accurate historical record, and on this basis examines the factors of sect emergence, recruitment, leadership and authority, internal sect structure, informal elites, coherence of sect values, group commitments and the sect's relation to the world. The early life of the founder, Charles Taze Russell, is discussed and the personal influence of some of his contemporaries is investigated in an attempt to trace the ideological origins of Russell's beliefs. His theology is briefly discussed, and the importance of the doctrines pertaining to the spiritual elite and character development is stressed. The subsequent development of the sect is then seen as the interrelation of structural and symbolic elements in a dynamic historical context. Russell's sect emerged as a schismatic group in 1879 and consisted of a community of Bible students in locally governed ecclesias. They were originally a loosely organised, ill-defined group but their habituated association, the sacralising of their activities and the growing opposition from outside combined to change them into a consciously separated sect in 1916. Russell's attempts to promote evangelisation through his Watch Tower Society, the enhancement of his own status as leader, the lack of an authority structure and the existence of informal elites were all factors that helped to cause the schisms of 1894 and 1908 in the sect, which clarified his status and authority respectively. The lack of an authority structure in the sect and the disconfirmation of the date 1914 (when God had been expected to take the faithful to heaven) led to severe structural and ideological strains, and Russell's movement split into different groups after his death, each emphasising a part of his message. Amongst these schismatic offshoots were the Pastoral Bible Institute who catered for an introversionist perspective involving individual character development, the Laymen's Home Missionary Movement who emphasised the exegetical and doctrinal complexity purveyed by a charismatic leader and the Dawn Bible Students Association who catered for those elements in Russell's following who were prone to move towards a denominational position. Russell's Watch Tower Society, under its second President Joseph P. Rutherford, emphasised evangelisation and a centrally controlled sect structure. Rutherford first gained absolute control of the Society headquarters and then, from 1919 to 1931, extended his control to the ecclesias, by displacing the elected elders. He succeeded in changing the sect beliefs, norma and values, patterns of evangelisation and worship, internal structure, group commitments and membership. The result was a new sect, Jehovah's Witnesses as they were named in 1931. There was a decrease in membership at this time partly due to the sect's involvement with the law and United States communities over the Flag Salute and other issues. During the second World War, however, the membership of the sect increased rapidly and has continued rising ever since to the present total of one and a half million. Since 1942 the Witnesses, under the third Watch Tower Society president Nathan H. Knorr, have engaged in a widespread training campaign whose purpose has been the socialisation of new converts and their training to maintain the high rate of recruitment to the sect. The Bible student community, on the other hand, has not increased in number and has no wish to. The thesis concludes with a brief discussion of the problems of charisma, schism and typological categories in relation to the sects discussed earlier in the thesis. Tentative conclusions are reached as to the likely future development of the groups that stem from C.T.Russell, including Jehovah's Witnesses.